Manifestation of suffering and resistance to the illness process in work management - Brant, Luiz Carlos; Minayo-Gomez, Carlos (Saúde e Sociedade, 2009)
The present article aims to identify and understand resistance forms based on suffering manifestations in work management. We undertook an investigation in a public company from the services sector, located in a metropolis of the Southeastern region of Brazil. We conducted open interviews with workers, managers, and health professionals from this company. For the analysis of the obtained accounts, we used dialectical hermeneutics as the methodological strategy. We found that some of the suffering conceptions in the specialized literature relegate the worker to the position of victim or sick person, neglecting his capacity for resistance and the positiveness deriving from the suffering manifestation. The accounts revealed the existence of reactive resistance, which emerged through cathartic and ambivalent forms, and of active resistance. We concluded that the reactive forms create minimum conditions for permanence in the job, and can prevent the sick person stigma, but they are not able to prevent situations which favor suffering. In fact, in the management sphere, the existence of the illness process in the workplace is not recognized, nor are its devices of attribution of the sick person's identity. The theoretical models that guide services evaluations do not take into account the benefits and advances coming from the different forms of resistance.